ENGLISH ROLE AS INTERNATIONAL LANGUAGE IN EDUCATION ON UNIVERSITY LEVEL - Ulya Himawati (Universitas Islam Nahdlatul Ulama Jepara, 2018)
Recently, the biggest problem of the university, especially Wahid Hasyim University is lack of lecturer who can speak English. Here, English is an international language that should be mastered by the lecturer at the university level. Many foreign students learn at Wahid Hasyim University. Although foreign students have been given lessons about the Indonesian language for one year before, in reality, they are still difficult to understand subject in Indonesia language which is not their own and universal language. Therefore, the lecturer should afford explanation subject in English when foreign students have not understood in Indonesia language. It shows that English is increasingly needed at the university level, not just for writing international journals but is needed in everyday life i.e. speaking. Thus, in order to compete in this millennial era, teaching staff need to practice and improve their English with the basic knowledge of speaking and how to apply it in learning. Furthermore, the university should hold an English course for teaching staff, so the teaching staff can apply English in the classroom. Thus, the teaching staff can make the foreign students become more comfortable and understand in the classroom.